Simplified Enzyme-Linked Immunosorbent Assay for Routine Identification of Rhizobium japonicum Antigens - Fuhrmann, J. (1985)
A simple, reliable, and flexible modification of the indirect enzyme-linked immunosorbent assay was developed for the identification of Rhizobium japonicum antigens from cultures and nodules. The procedure emphasizes efficient use of time and reagents, adaptability to variously equipped laboratories, and maintenance of sensitivity levels that are adequate for ecological studies.